Nutrient analysis of three low-carbohydrate diets differing in carbohydrate content - Banner, Lani; Rice Bradley, Beth H.; Clinthorne, Jonathan (Frontiers in Nutrition, 2024)
Low-carbohydrate diets are increasing in popularity. Despite clinical evidence demonstrating their safety and efficacy, concerns regarding the nutrient adequacy of low-carbohydrate diets persist. The aims of this study were to assess the nutrient adequacy of three seven-day meal plans that delivered 20 (VLCD20), 40 (VLCD40), and 100 (LCD100) grams of net carbohydrate per day, respectively. Nutrient analyses were conducted using USDA Food Data Central. All three low-carbohydrate meal plans exceeded recommendations for vitamins A, C, D, E, K, thiamin, riboflavin, niacin, B6, folate and B12 in males and females 31-70 years and exceeded calcium recommendations for adults 31-50 years but remained below the Tolerable Upper Intake Level. VLCD40 and LCD100 met or exceeded fiber recommendations for females ages 31-70 years and were adequate for males 51-70 years. None of the meal plans contributed meaningful amounts of added sugar. The plans exceeded the Recommended Dietary Allowance for protein for adults ages 31-70 years of age but were within the Acceptable Macronutrient Distribution Range of 10-35% of energy. The plans slightly exceeded recommendations for saturated fat and sodium but were lower in these nutrients than the average American diet and had more favorable omega-6 to omega:3 and sodium to potassium ratios than is typical. All three meal plans met or exceeded the Estimated Average Requirement for micronutrients in females ages 31-50 years, the population group most likely to consume low-carbohydrate diets. Well-constructed low-carbohydrate meal plans can be nutritionally adequate in adults.